The Role of Logistics Service Providers in Large Scale Construction Projects - Stein, Benjamin (2013)
The construction industry unlike other industries such as manufacturing has a difficult time adopting ‘best practices’ to improve upon their processes on and off the construction sites. Especially logistics management for construction projects is assumed to have the potential for significant cost savings. Reasons for a slow progression can be seen within the fragmented industry with many parties involved in carrying out a project and the relationships throughout the whole supply chain. In order to resolve these issues this research aims at what specific role logistics service providers play in construction projects and what would be needed to be done to assist in implementing change and in order to advance forward. The review of the issues in the industry, case studies and of logistic service providers suggests that there are a lot of opportunities in an integrated logistics management approach. Highlighted is hereby in particular the measurement, analysis and processing of information as well as the necessity for coordination and collaboration in the supply chain. Finally a framework is developed from a project management view of the implementation of logistics management and its providers.